The Creative Tourist Experience in the Alentejo region: A case study of the CREATOUR project in Portugal - MARUJO, NOÉMI (2021)
Tourism demand for culture-based creative tourism has been triggering growing interest in various research domains. In the context of the CREATOUR project ‘Creative Tourism Destination Development in Small Cities and Rural Areas’, an exploratory study was conducted in order to describe and analyse the tourist experience in the pilot activities carried out. The profile of the tourists that participated in the creative tourism activities promoted by the CREATOUR pilot in the Alentejo Portuguese region will be under review concerning sociodemographic characteristics, travel behaviour and motivations. To accomplish this objective, a total of 74 surveys were collected in 2018. Results revealed that participants in creative activities are of an active professional age, have a higher level of qualifications and travel with their partners or in an organised group. Regarding their motivations, results also revealed that they seek original experiences and want to stimulate more creative behaviour.